Postoperative cerebral hemorrhage death in a patient with secondary hyperparathyroidism: a report of one case and literature review - Zhou, Peng; Xu, Jing; Zhuang, Dayong; Li, Xiaolei; Yue, Tao; Hu, Huaiqiang; He, Qingqing (Frontiers in Neuroscience, 2023)
Secondary Hyperparathyroidism (SHPT) is a common complication of end-stage renal disease (ESRD), and parathyroid surgery (PTX) is an effective way to treat patients with severe SHPT. ESRD has multiple associations with cerebrovascular diseases. For example, the incidence of stroke in patients with ESRD is 10 times higher than that in the general population, the risk of death after acute stroke is three times higher, and the risk of hemorrhagic stroke is significantly higher. High/low serum calcium, high PTH, low serum sodium, high white blood cell count, previous occurrences of cerebrovascular events, polycystic kidney disease (as a primary disease), and the use of anticoagulants are independent risk factors for hemorrhagic stroke in hemodialysis patients with uremia. The risk of stroke in patients who undergo PTX decreases significantly in the second year of follow-up and persist thereafter. However, studies on the risk of perioperative stroke in SHPT patients are limited. After undergoing PTX, the PTH levels in SHPT patients drop suddenly, they undergo physiological changes, bone mineralization increases, and calcium in the blood gets redistributed, often accompanied by severe hypocalcemia. Serum calcium might influence the occurrence and development of hemorrhagic stroke at various stages. To prevent bleeding from the operated area, the use of anticoagulants after surgery is reduced in some cases, which often decreases the frequency of dialysis and increases the quantity of fluid in the body. An increase in the variation in blood pressure, instability of cerebral perfusion, and extensive intracranial calcification during dialysis promote hemorrhagic stroke, but these clinical problems have not received enough attention. In this study, we reported the death of an SHPT patient who suffered a perioperative intracerebral hemorrhage. Based on this case, we discussed the high-risk factors for perioperative hemorrhagic stroke in patients who undergo PTX. Our findings might help in the identification and early prevention of the risk of profuse bleeding in patients and provide reference for the safe performance of such operations.